PENGARUH INTERNETBANKING, MOBILE BANKING DAN ATM TERHADAP KEPUASAN NASABAH BANK PANIN DI KOTA BATAM - maria paula dadha, maria paula dadha (LPPM Universitas Putera Batam, 2023)
Currently, banks have introduced Internet Banking, Mobile Banking and ATMs to improveservice quality and gain satisfaction in transactions. Despite all efforts aimed at developingbetter and easier information technology, information technology in general is not paidattention to and utilized by customers. Therefore, an understanding of customeracceptance of information technology is needed and the need to identify factors that canfacilitate customer transactions at banks, namely through ATMs, internet banking andmobile banking. Based on the background of the problem above, the formulation of theproblem in this study is how the influence of Internet Banking, Mobile Banking and ATM onPanin Bank customer satisfaction both partially and simultaneously. This type of researchis a field research (Field Research). seen from the nature of this research is descriptiveanalysis. Data collection techniques using questionnaires, documentation and literaturestudy. The analytical method used is a quantitative descriptive approach. The researchvariable consists of the dependent variable, namely satisfaction (Y) and the independentvariable, namely Internet Banking (X1), Mobile Banking (X2), and ATM (X3). The collecteddata were analyzed using multiple linear regression analysis